PISM-LakeCC: Implementing an adaptive proglacial lake boundary into an ice sheet model - Hinck, Sebastian; Gowan, Evan J.; Zhang, Xu; Lohmann, Gerrit (Copernicus Publications (EGU), 2020)
Geological records show that vast proglacial lakes existed along the land terminating margins of palaeo ice sheets in Europe and North America. Proglacial lakes impact ice sheet dynamics by imposing marine-like boundary conditions at the ice margin. These lacustrine boundary conditions include changes in the ice sheet’s geometry, stress balance and frontal ablation and therefore affect the entire ice sheet’s mass balance. This interaction, however, has not been rigorously implemented in ice sheet models. In this study, the implementation of an adaptive lake boundary into the Parallel Ice Sheet Model (PISM) is described and applied to the glacial retreat of the Laurentide Ice Sheet (LIS). The results show that the presence of proglacial lakes locally enhances the ice flow. Along the continental ice margin, ice streams and ice lobes can be observed. Lacustrine terminating ice streams cause immense thinning of the ice sheet’s interior and thus play a significant role in the demise of the LIS. Due to the presence of lakes, a process similar to the marine ice sheet instability causes the collapse of the ice saddle over Hudson Bay, which blocked drainage via the Hudson Strait. In control experiments without a lake model, Hudson Bay is still glaciated at the end of the simulation. Future studies should target the development of parametrizations that better describe the glacial-lacustrine interactions.